الإعلام التّربوي ودوره في الحد من مظاهر الفساد الاجتماعي Educational media and its role in reducing the aspects of social corruption - بوعرعوري, هشام (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف هذه الدّراسة إلى التّعرف على الدّور الذي تلعبه وسائل الإعلام في التّوعية التّربوية للحد من مظاهر الفساد الاجتماعي، وأهمية الدور الذي تؤديه وسائل الاتصال الجماهيري كطرف فعّال ومهم في نجاح عملية بناء شخصية الأفراد، لما تتمتع به من مميزات وخصائص تأثر بشكل واضحٍ وكبير على تشكيل البناء السّلوكي، الإدراكي، والمعرفي للفرد والمجتمع، باعتبارها منافساً للمؤسسات الاجتماعية "كالأسرة والمدرسة"، تساهم في عملية التّنشئة الاجتماعية تجاه قضايا مجتمعية معينة، لإكساب الأفراد القدرة على تحليلها واستيعابها ولنشر نمط سلوكي إيجابي، ثقافي، واجتماعي ينتهجه، لترسيخ القيم الأخلاقية فيه كوسيلة للتصدي لكل مظهر من مظاهر الفساد الاجتماعي. Abstract: This study aims to identify the role that is played by the media in educational awareness to reduce the aspects of social corruption, and the importance of the role that is played by mass communication as an effective and important element in the success of the process of building the personality of individuals, because of its advantages and characteristics that have a clear and significant impact on the formation of the building behavioral, perceptual, and cognitive of the individual and society, as it competes with social institutions such as the family and the school, and contributes to the process of socialization towards specific societal issues, to give individuals the ability to analyze and absorb them and to spread a positive, cultural, and social behavioral pattern that they follow, to instill moral values in them as a means to address all manifestation of social corruption